Refactoring a Python script into a library called by Python Click CLI. (Pragmatic AI Solutions, 2022)
Learn to refactor a Python script into a library called by Python Click CLI. 00:00 Intro 00:19 Refactoring to a library 01:44 Installing click 02:23 Importing refactored library 02:36 Building click options 05:04 Formatting code with Python Black and Running Click 06:14 Building conditional logic to print colored output.